Yellowish and blue luminescent graphene oxide quantum dots prepared via a microwave-assisted hydrothermal route using H2O2 and KMnO4 as oxidizing agents. (20th December 2017) - Hu, Chechia; Su, Tzer-Rurng; Lin, Tzu-Jen; Chang, Chien-Wei; Tung, Kuo-Lun
Abstract : Microwave-assisted hydrothermal synthesized GOQDs exhibit yellowish-green and blue light emission with quantum yields of 15.1% and 8.4%, respectively. Abstract : Graphene oxide quantum dots (GOQDs) with different oxygenation levels were successfully prepared using a facile, rapid, and cost-effective microwave-assisted hydrothermal method under neutral conditions using hydrogen peroxide (MGOH) or potassium permanganate (MGOK) as an oxidizing agent. GOQDs with an average diameter of 7–12 nm for both MGOH and MGOK samples were observed using transmission electron microscopy (TEM). X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) analyses revealed that MGOH exhibited a high quantity of C–O and CO groups in its structure, whereas MGOK consisted of highly ordered sp 2 /sp 3 bonds in its aromatic unit and had less oxygenated functional groups. The photoluminescence measurements showed that MGOH and MGOK QDs emitted yellowish-green and blue light with quantum yields of 15.1% and 8.4%, respectively. The luminescence mechanisms of MOGK and MGOH were attributed to π–π* and n–π* electron transitions in C–C/CC bonds and in π* states to non-bonding oxygen states, respectively. Density functional theory calculations were employed to determine the optical absorption of GOQDs in terms of surface functional groups and oxygenation degrees. Theoretical calculations demonstrate that the high oxygenation degree of GOQDs resulted in band gap reduction and light absorption due to electron transitions. Our theoretical and experimental results suggested that GOQDs with high quantum yields can serve as promising materials in applications including biosensing, imaging, and labeling.